2012
DOI: 10.2528/pierc12012601
|View full text |Cite
|
Sign up to set email alerts
|

Compact Reconfigurable Uwb Antenna Integrated With Stepped Impedance Stub Loaded Resonators and Switches

Abstract: Abstract-A compact reconfigurable antenna integrated with stepped impedance stub (SIS) loaded stepped impedance resonator (SIR) and SIS loaded hexagon stepped impedance resonator (HSIR) for ultra wideband (UWB) applications is proposed in this paper. The reconfigurable UWB antenna can work as a UWB antenna and a dual notch band UWB antenna by controlling the switches ON and OFF. The proposed two notch bands are obtained by embedding a SIS-HSIR on hexagon radiation patch and a SIS-SIR on coplanar waveguide (CPW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…This can be addressed with antennas designed to accommodate one or several rejections [6–8]; such frequency rejections prevent spurious signals from either entering the system or being emitted by it, thus ensuring the electromagnetic compatibility of UWB systems with legacy ones. However, the rejections are usually permanent and fixed in the antenna hardware, whereas flexibility could be obtained through rejection tuning or rejection switching [9–11].…”
Section: Introductionmentioning
confidence: 99%
“…This can be addressed with antennas designed to accommodate one or several rejections [6–8]; such frequency rejections prevent spurious signals from either entering the system or being emitted by it, thus ensuring the electromagnetic compatibility of UWB systems with legacy ones. However, the rejections are usually permanent and fixed in the antenna hardware, whereas flexibility could be obtained through rejection tuning or rejection switching [9–11].…”
Section: Introductionmentioning
confidence: 99%
“…From Table 3 it is found that the geometry offers the maximum impedance bandwidth of 124%. Also, the defected ground behind the monopole geometries offer a wide impedance bandwidth [14][15][16][17], in this work we have included a finite ground of size equal to L g x W s . Width of the ground is chosen equal to the substrate width and length is chosen such that it covers only feed line of the monopole antenna.…”
Section: Effect Of Radius and Ground Dimensionsmentioning
confidence: 99%